KONSELING GIZI DENGAN MEDIA BUKU SAKU BERPENGARUH TERHADAP PENGETAHUAN DAN INTAKE NATRIUM PADA PASIEN CHRONIC KIDNEY DISEASE (CKD) DI RS ROEMANI SEMARANG - Dominico Surya Febri Mulyanto; Wiwik Wijaningsih; Yuniarti Yuniarti (Poltekkes Kemenkes Semarang, 2019)
Background: Chronic Kidney Disease (CKD) is a protection program for a period of months or years. CKD patients who do the required HD, the amount of medication and normal sodium intake that are not working normally. Fluid and sodium intakes are one of the factors needed in the management of kidney failure to prevent complications due to edema, hypertension, and cardiovascular disease.Objective: To find out nutritional counseling on knowledge and sodium intake in Chronic Kidney Disease Patients (CKD) who underwent Hemodialysis at Roemani Hospital Semarang.Method: This study included a quasi experimental study with a Non Randomized Pretest Posttest Control Group research design. Sampling was 15 people in the treatment group and 15 people control group. Interventions provided include nutritional counseling with pocket book media. intake data collection was taken by interview using SQ-FFQ and knowledge data was taken by questionnaire. Results with paired t-test and independent t-test with a significance level of 0.05.Result: There is an effect of nutritional counseling with the media of pocket books on knowledge and sodium intake. Knowledge of respondents in the intervention group increased 22.33 and decreased sodium intake by 77.4. Conclusion: The provision of nutritional counseling using an influential pocket book increases knowledge and lowers intake compared to just giving a pocket book